Melancholy and the archive - Boulter, Jonathan (Continuum, 2011)
Introduction – Part I: The Material Archive – 1. Archiving Trauma: Paul Auster – 2. Burying History: Haruki Murakami – Part II: The Imaginary Archive – 3. Humanizing History: David Mitchell – 4. Archiving Melancholy: Jose Saramago – Conclusion – Bibliography – Index
10.5040/9781472542632
Keywords: Fiction; Memory in literature; Melancholy in literature